2019
DOI: 10.1186/s13045-019-0699-4
|View full text |Cite
|
Sign up to set email alerts
|

Tumor stem-like cell-derived exosomal RNAs prime neutrophils for facilitating tumorigenesis of colon cancer

Abstract: BackgroundCell-cell interactions maintain tissue homeostasis and contribute to dynamic alteration of the tumor microenvironment (TME). Communication between cancer and host cells not only promotes advanced disease aggression but also determines therapeutic response in cancer patients. Despite accumulating evidence supporting the role of tumor-infiltrating immunocytes in modulating tumor immunity, the interplay between heterogeneous tumor subpopulations and immunocytes is elusive.MethodsWe expanded colorectal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(105 citation statements)
references
References 63 publications
2
102
0
1
Order By: Relevance
“…Exosomes, membrane vesicles of endocytic origin ranging in size from 30 to 150 nm approximately, are emerging as key players in intercellular communication between cancer cells and their microenvironment [5]. A distinct feature of exosomes is that they efficiently carry and deliver molecular signatures (proteins, lipids, RNA…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes, membrane vesicles of endocytic origin ranging in size from 30 to 150 nm approximately, are emerging as key players in intercellular communication between cancer cells and their microenvironment [5]. A distinct feature of exosomes is that they efficiently carry and deliver molecular signatures (proteins, lipids, RNA…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9) are well established tumor markers with low sensitivity and specificity for early detection of CRC [4]. Hence, ideal CRC-specific biomarkers are urgently required to improve the current CRC diagnostic strategies.Exosomes, membrane vesicles of endocytic origin ranging in size from 30 to 150 nm approximately, are emerging as key players in intercellular communication between cancer cells and their microenvironment [5]. A distinct feature of exosomes is that they efficiently carry and deliver molecular signatures (proteins, lipids, RNA…”
mentioning
confidence: 99%
“…For example, it was reported that glioblastoma stem cell-derived exosomes direct monocytes toward the immune suppressive "M2" phenotype, through the signal transducer and activator of transcription-3 (STAT3) pathway, creating an immunosuppressive microenvironment (Gabrusiewicz et al, 2018). While colorectal cancer stem cellderived exosomes promote a pro-tumoral phenotype in neutrophils by increasing interleukin-(IL)-1b expression (Hwang et al, 2019) Since tumor-host cross-talk is believed to be initiated by CSCs, and communication between cancer cells and other cells is conducted through exosomes, it's of great importance to take a closer look at the role of CSCs-exosomes, and its involvement in Western Blot analysis revealed up regulation of PD-L1 in exosome-treated monocytes. PD-L1 correlates with increased STAT3 pathway phosphorylation, which mediate this immune suppressive switch.…”
Section: What Is Proposed?mentioning
confidence: 99%
“…(Gabrusiewicz et al, 2018) Exosomes derived from spheroid formations of colorectal cancer cell line Prompted a pro-tumoral phenotype in neutrophils miRNA and ELISA analysis revealed elevated levels of IL-1b in exosometreated neutrophils and their condition medium. (Hwang et al, 2019) PTEN, phosphatase and tensin homolog; MALTA1, metastasis associated lung adenocarcinoma transcript 1; PD-l1, programmed death-ligand 1; ELISA, enzyme-linked immunosorbent assay.…”
Section: What Is Proposed?mentioning
confidence: 99%
“…Very recently, the same group demonstrated that CRC patients, who expressed the specific CRCSC activation pattern Snail + /IL-8 + , display increased MyeloPerOxidase (MPO) + neutrophils which correlate with poor patient survival [63] . According to these data, Roncucci et al [64] showed that patients with CRC display higher number of MPO + cells in normal mucosa rather than controls, and that MPO + levels increase during carcinogenesis.…”
Section: Il-8 Involvement In Crc Stem Cellsmentioning
confidence: 99%